Innovations in capture fisheries are an imperative for nutrition security in the developing world - Hall, Stephen J.; Hilborn, Ray; Andrew, Neil L.; Allison, Edward H. (National Academy of Sciences, 2013)
This article examines two strands of discourse on wild capture fisheries; one that focuses on resource sustainability and environmental impacts, another related to food and nutrition security and human well-being. Available data and research show that, for countries most dependent on fish to meet the nutritional requirements of their population, wild capture fisheries remain the dominant supplier. Although, contrary to popular narratives, the sustainability of these fisheries is not always and everywhere in crisis, securing their sustainability is essential and requires considerable effort across a broad spectrum of fishery systems. An impediment to achieving this is that the current research and policy discourses on environmental sustainability of fisheries and food security remain only loosely and superficially linked. Overcoming this requires adoption of a broader sustainability science paradigm to help harness synergies and negotiate tradeoffs between food security, resource conservation, and macroeconomic development goals. The way society chooses to govern fisheries is, however, an ethical choice, not just a technical one, and we recommend adding an ethical dimension to sustainability science as applied to fisheries.